Problemas relativos a la evaluación investigadora de los profesores universitarios del área de Biblioteconomía y Documentación - López Yepes, José; Ros García, Juan (Revista General de Información y Documentación, 2003)
It is a fact of today’s scientific culture that the quality of research carried out by academics and professionals is being continuously assessed. This article reviews the various stages in which this research activity is assessed by the different public administrations and analyses the most popular evaluation methods employed, including peer review, publication in prestigious journals and the normative criteria required to evaluate the quality of doctoral dissertations. Finally, the author proposes a new set of evaluation criteria based on quality citation received by the authors undergoing the assessment with a view to determining their real contribution to their scientific field.